2009
DOI: 10.1103/physreva.79.033830
|View full text |Cite
|
Sign up to set email alerts
|

Angular momentum of focused beams: Beyond the paraxial approximation

Abstract: We investigate in detail the focusing of a circularly polarized Laguerre-Gaussian laser beam ( ℓ orbital angular momentum per photon; σ = 1/ − 1 for left/right-handed polarization) by a high numerical aperture objective. The diffraction-limited focused beam has unexpected properties, resulting from a strong interplay between the angular spatial structure and the local polarization in the non-paraxial regime. In the region near the beam axis, and provided that |ℓ| ≥ 2 and ℓ and σ have opposite signs, the energy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
104
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(112 citation statements)
references
References 41 publications
(67 reference statements)
6
104
2
Order By: Relevance
“…In order to avoid any possible ambiguity that may arise from the AM density [30,31], I do not use this notion here. In fact, we have given in Eqs.…”
Section: Am Properties Of Non-paraxial Beamsmentioning
confidence: 99%
“…In order to avoid any possible ambiguity that may arise from the AM density [30,31], I do not use this notion here. In fact, we have given in Eqs.…”
Section: Am Properties Of Non-paraxial Beamsmentioning
confidence: 99%
“…Regarding the magnitude of the fields near r = 0 Zurita-Sánchez et al [30] have shown that, for the strongly focused azimuthally- polarized beam they studied, the magnetic interaction overcomes the electric interaction near the phase singularity; recently, their findings have been corroborated by the theoretical study of Klimov et al [49] in the case of focused Laguerre-Gaussian beams. Finally, in their research on highly-focused TL beams, Monteiro et al [63], Iketaki et al [59] and Klimov et al [49] report that interesting effects only occur when ℓ = 1, 2 and σ = −1. The overall similarities are no coincidence, for the vector potential Eq.…”
Section: Figmentioning
confidence: 97%
“…The intrinsic photonic SOI effect can also happen in nonparaxial light, e.g., light scattering by small particles136–144 (Figure 5c), or light focusing by high numerical aperture (NA) lenses136,145–151 (Figure 5d), or a combination of the focusing and scattering processes in high NA imaging of small particles 136. The SAM‐IOAM interaction in this effect can generate spin‐dependent optical vortex and thus induce SOAM conversions 137,140,146,147,149,150,152–154.…”
Section: Photonic Spin–orbit Interactionsmentioning
confidence: 99%